A systematic review of the factors influencing the motivation to lead among students in higher education - Amadi, Winston Aligbaso; Du Plessis, Marieta; Balogun, Tolulope Victoria (Frontiers in Education, 2025)
IntroductionInstitutions of higher education are considered a grooming ground for future leaders in the workplace and society at large. Several reasons can be attributed to why students are motivated to engage in leadership within these institutions. Research on motivation to lead highlights variables such as personality, values, leadership self-efficacy (LSE), and leadership experience as antecedents of motivation to lead.MethodsTo identify other factors that could influence students’ motivation to lead, this paper reviewed published research from 2001 to 2024 investigating higher education students’ motivation to lead. The study included 13 articles that met the criteria for inclusion.ResultsThematic analysis was carried to identify the factors and then categorized the identified factors into internal and external factors to the students in the higher education environment. This was done based on the self-determination theory on motivation highlighting intrinsic and extrinsic motivators to human behavior.DiscussionInternal factors include emotion perception, race, need for power, affiliation and accomplishment, emotional intelligence, and LSE. External factors include leadership courses, programs and training, opportunities to lead, involvement in co-curricular clubs, campus support for leadership development, and classroom-based team experiences. This categorization aims to facilitate the design of interventions to enhance students’ motivation to engage in leadership activities and assume leadership roles. Limitations of this study include the small number of analysed studies, limited geographic representation, and restriction to English-language articles only.